Palladium recovery from spent Pd plating solutions using Lewatit TP 214 resin - ÇETİNER, BURCU NİLGÜN; AKTAŞ, SERDAR (My University, 2022)
This study aims to explore the recovery of palladium (Pd(II)) ions using Lewatit TP 214 resins. Waste Pd(II) ions with ammonia complex procured from a precious metal plating were selected as the source solution. In the experimental studies, two stock solutions of 60 ppm Pd(II) with a pH value of 4.0 and 7.5 were prepared as initial solutions. The experiments were performed by altering four parameters: solution pH, time 15-180 min, temperature 25 degrees C-60 degrees C, and amount of resin 100-400 mg. It was proved that the recovery percentage increased with higher temperature and resin at lower pH values. The Pd(II) recovery percentage increased with a temperature rise, reaching 100% after 40 min at pH 4.0 and 60 degrees C. On the other hand, a bit lower efficiency (95%) was attained after 180 min at pH 7.5 and 60 degrees C. Using Lewatit TP 214, the computed activation energies for Pd(II) recovery are 17.73 and 15.62 kJ/mol at pH 4.0 and 7.5, respectively. Considering these activation energy values, a mixed mechanism dominated the recovery of Pd(II).
Keywords: Tarımsal Bilimler; Ziraat; Toprak ve Bitki Besleme; Toprak ve Su Muhafazası ve Amenajmanı; Havza Yönetimi; Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Soil and Plant Feed; Soil and Water Storage and Management; Watershed Management; Chemical Engineering and Technology; Engineering and Technology; MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); SU KAYNAKLARI; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); WATER RESOURCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Genel Mühendislik; Su Bilimi ve Teknolojisi; Kimyasal Sağlık ve Güvenlik; Akışkan Akışı ve Transfer İşlemleri; Kimya Mühendisliği (çeşitli); Mühendislik (çeşitli); Genel Kimya Mühendisliği; Kolloid ve Yüzey Kimyası; Kataliz; Fizik Bilimleri; General Engineering; Water Science and Technology; Chemical Health and Safety; Fluid Flow and Transfer Processes; Chemical Engineering (miscellaneous); Engineering (miscellaneous); General Chemical Engineering; Colloid and Surface Chemistry; Catalysis; Physical Sciences; Palladium recovery; Waste plating solution; Ion-exchange resin; Lewatit TP 214; ION-EXCHANGE-RESINS; CHLORIDE SOLUTIONS; FUNCTIONAL-GROUPS; ADSORPTION; COMPLEXES; REMOVAL; MEDIA